Bacteriophages: Bacteriófagos - Domínguez Navarrete, Nicanor (2019)
Viruses that parasitize bacteria, called bacteriophages or phages, are returning to scientific news, evidenced by the creation of the Howard Hughs Medical Institute in the United States (USA), or the CRU-MEDI Institute in the United Kingdom; This change of interest is due to the possibility of using them in antibacterial therapy, against multiresistant bacteria. The knowledge of these viruses begins with the studies of Frederick Twort in the year 1915, demonstrating that "there are viruses that infect bacteria and kill them." But it was Felix d'Herelle, who successfully developed therapeutic protocols for digestive infections in animals and humans. Bacteriophages have been the basic laboratory tool for the development of science in virology and molecular biology.